FACTORS OF VILLAGE STATE-OWNED COMPANY ARE IN ACTIVE IN JAMBI PROVINCE - Tona Aurora Lubis; Firmansyah Firmansyah (Management Department, Faculty of Economics and Business, Universitas Jambi, 2020)
This study aims to formulate a model of the inactive Village State-Owned Company factors in Jambi Province. This type of research is a type of qualitative research with a phenomenological type. This qualitative research analysis was assisted by using the Nvivo qualitative research software. Based on the research results, it can be concluded that the main factors causing the inactivity of BUMDes in Jambi province can be divided into 3, which are BUMDes management factors, village officials, and the community.